The use of the future participle tense in κοινή Greek of the New Testament (Theological Kronos, 2022)
Numerous commentaries, grammars, and academic studies have noted the importance of the participle for New Testament κοινή. Widely recognized is the fact that the future participle is rare in the New Testament. However, this grammatical form is found among various New Testament authors. The objective of this study is to examine the ways in which future participles function as part of literary structures and the implications for New Testament exegesis.
Keywords: Greek; New Testament; Participle; Grammar; κοινή